Flexible phenotypes: the diverse roles of phenotypic plasticity during adaptive evolution in experimental populations of Trinidadian guppies - Handelsman, Corey, author; Ghalambor, Cameron, advisor; Angeloni, Lisa, committee member; Antolin, Michael, committee member; Myrick, Christopher, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Keywords: adaptive evolution; experimental evolution; local adaptation; phenotypic plasticity; plasticity; rapid evolution